Determination of the optode array representation using optical properties at systole and diastole - Jumadi, Nur Anida (Institute of Physics, 2013)
The necessity to develop an optode array in order to probe the fetus oxygenation noninvasively regardless of the fetus position has been highlighted in previous literature. In this paper, a series of optical simulations are carried out to determine the best representation of optode array by using optical properties at systolic and diastolic states. The selection is based on the highest flux values accumulated at respective detectors. To accomplish the objective, a homogenous three-layer semi-infmite tissue model is implemented to represent the pregnant woman model. The geometry of the model as well as Monte Carlo simulation are carried out using commercial software, whereas the optical properties related to systolic and diastolic states are defined for all wavelengths. A statistical noise analysis is also introduced in order to find a sufficient number of rays to be launched into the optical tissue system.